DUA DINASTI DI KERAJAAN MATARĀM KUNA: Tinjauan Prasasti Kalasan - Hariani Santiko (Jurnal Sejarah dan Budaya, 2013)
Abstract. Who was the ruler at center of Java in 8th-10th centuries at Ancient Mataram Kingdom is still a debatable problem. There are two opinion groups. The one opinion states that there are two dynasties (Sanjaya dynasty and Syailendra dynasty), and the other opinion declares only one dynasty based on assumption Rakai Panagkaran, The son of King Sanjaya, changed his religion to Buddha Mahayana. Based on retranslation inscription of Kalasan, there were two kings on this inscription, namely Śri Mahārāja Dyah Pañcapanam Panamkarana and King Śailendravamsatilaka that was remain as “raja bawahan” (“lower king”) of Śri Mahārāja Dyah Pañcapanam Panamkarana who still had Siwa religion. Rakai Panangkaran was remain as King of Sanjaya Dynasty (Sanjayavamśa) and Śailendravamsatilaka was becoming a king in his “Growing Kingdom”.